How do i solve each proportion?
How do i solve each proportion? - 1

Answers

Answer 1
Answer: You have to cross multiply (multiply the numerator of the first by the denominator of the second and the numerator of the second by the denominator of the first).

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

[19]

(x+4)/(3) = (4)/(10)

10x+40=12

10x = -28

x=-2.8

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

[21]

(4)/(n+8) = (10)/(8)

32 = 8n + 64

8n = -32

n=-4
Answer 2
Answer: 19) (x + 4)/(3) = (4)/(10) \n \n x + 4 = (4)/(10) * 3 \n \n x = 1.2 - 4 = -2.8 \n \n x = -2.8 \n \n \n 20) (4)/(n+8) = (10)/(8) \n \n 32 = 8n + 64 \n \n 8n = 32 -64 = -32 \n \n 8n = -32 \n \n n = -4

Related Questions

(write the slope-intercept form of the equation of each line) helllpppppp- pls-
If the length of a rectangle isexpressed by 22 + 41-8 and thewidth is 3x What is the area of therectangle?
Advance tickets for a school play went on sale. The price of each student ticket was $4 and everyone else paid $5. On the first day, no more than $80 in tickets were sold. Describe and explain the possible values of s, the number of student tickets sold, and e, the number of tickets sold to nonstudents.
Convert: 25 pints (liquid) to liters.
As shown in the diagram below, CD is a median of triangle ABC.

How many whole dollars can you make with 248 pennies? how many cents are left over

Answers

two dollars: and 48 cents will be left over
2 dollars 48 cents
There is 100 cents in a dollar. 

Identify the number of solutions or zeros

2x^2+5x-9=0

Answers

There are going to be two solutions because the "biggest" x is x^2 but you can factor to find what they actually are.

Final answer:

The quadratic equation 2x^2+5x-9 = 0 has two solutions or zeros, which may be real or complex. They can be found using the quadratic formula: x = [-5 + sqrt(97)]/4 and x = [-5 - sqrt(97)]/4.

Explanation:

The equation given is 2x^2+5x-9=0, which is a quadratic equation. The solutions or zeros of a quadratic equation can be found using the quadratic formula: x = [-b ± sqrt(b^2 - 4ac)]/2a. Here, a=2, b=5, and c=-9.

Let's substitute these values into the formula:

x = [-(5) ± sqrt((5)^2 - 4*2*(-9))]/2*2

x = [-5 ± sqrt(25 + 72)]/4

x = [-5 ± sqrt(97)]/4

Therefore, this equation has "two solutions" or zeros, which are x = [-5 + sqrt(97)]/4 and x = [-5 - sqrt(97)]/4.

Learn more about Quadratic Equations here:

brainly.com/question/30098550

#SPJ2

What is £300 divided into a ratio of 3:7

Answers

a) sum 3 + 7 =10
b) divide  £300 ÷ 10 =  £30
c) multiply:
     3 x 30 =  £90
     7 x 30 =  £210

Values are:  £90 and  £210



First you add the ratio  together 3+7=10 Then you do £300 divided by 10 = £30 
Then you do £30 X 3 (from the ratio in the beginning) which equals £90 
Then you do £30 X 7 (also from the ratio in the beginning) which equals £210 
The ratio is £90:£210 
Also you can add the ratios up so that it equals £300 the number you started with 
£90+£210=£300 
Hope I helped :)

The table shows the battery life of four different mobile phones.Mobile Phone Battery Life
Phone Battery Life
A 20
B 25
C 10
D 18


If 7.75% of the battery life of each mobile phone is used in a day by a typical user, for which mobile phone is 0.775 hour of battery life used in a day?
Phone A
Phone B
Phone C
Phone D

Answers

Answer:

Probably phone C

Step-by-step explanation:

Answer:

1. B

2. D

hope this helped

What fraction is equivalent to 11/24?

Answers

You can find equivalent fractions by multiplying both the numerator and the denominator by the same number.  An equivalent fraction to 11/24 could be 22/48.  Or 33/72, etc.

Final answer:

To find an equivalent fraction to 11/24, divide both the numerator and denominator by a common factor.

Explanation:

To find the fraction that is equivalent to 11/24, we need to find an equivalent fraction with a numerator and denominator that have a common factor with 11 and 24.

11 and 24 have a common factor of 1. So, if we divide both the numerator and denominator of 11/24 by 1, we get the equivalent fraction 11/24.

Learn more about Equivalent fractions here:

brainly.com/question/18040047

#SPJ2

M is the midpoint of YZ. If YM = x + 3, and YZ = 3x -1, find MZ

Answers

2(x+3)= 3x-1
2x+6=3x-1
X=7
Therefore
YM = 7+3= 10
And by definition of midpoint YM=MZ so MZ=10